Patients and informal caregivers' questions about alveolar bone graft post-operative care - Natiele Favarão da Silva; Marli Luiz Beluci; Fábio Luiz Banhara; Tatiane Henrique; Maila Meryellen Ferreira Garcia Manso; Armando dos Santos Trettene (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to identify patients' and informal caregivers' questions related to alveolar bone graft post-operative care. Methods: analytical and cross-sectional study, developed in a public and tertiary hospital between October 2017 and February 2018. The sample consisted of 46 participants. Data collection occurred during the preoperative nursing consultation through interview. The doubts were described in a form prepared by the researchers and later grouped by similarity of the subject. Results: doubts referred to diet (type of food, consistency, temperature and time period), surgical wound care (oral hygiene, graft rejection, removal of surgical points), post-operative complications (bleeding and edema), convalescence period (sun exposure, physical effort, time away from activities, length of stay) and medications. Conclusions: identifying the doubts allowed planning and implementing nursing care focused on the real needs of the clientele, favoring the rehabilitation process.